3055 Reconstruction of Patient-specific Distal Airway Regeneration Patterns in COPD. (27th March 2019) - Mahjour, Seyed Babak; Gomi, Kazunori; Rustam, Samir; Dolma, Phurbu; Krishnan, Jamuna; Elemento, Olivier; D'Ovidio, Frank; Blackwell, Timothy S.; Randell, Scott; Shaykhiev, Renat
Abstract : OBJECTIVES/SPECIFIC AIMS: The objective of this study was to reconstruct patient-specific distal airway patterns at the tissue- and single-cell resolution and develop personalized distal airway models based on utilization of patient-derived DABCs and autologous region-specific stromal cells. METHODS/STUDY POPULATION: Patient-specific distal airway units, containing parental small bronchiole (<2 mm in diameter, >12 th generation) and daughter airway branches, including pre-terminal/terminal bronchioles, leading to alveoli (3-7 units/lung), were dissected. Epithelial and stromal cells were isolated from these units and processed for ddSeq single-cell RNA-sequencing (n=6 samples). Autologous DABCs and stromal cells were isolated, propagated, biobanked, and used for establishment of patient-specific distal airway models (3D-organoids and air-liquid interface-based airway wall model; n=10 samples). Region-specific tissue patterns were evaluated using immunofluorescence and laser-capture microdissection (LCM; n=6 samples). RESULTS/ANTICIPATED RESULTS: Single-cell-based human distal airway transcriptome map (constructed based on the analysis of >6, 500 distal airway cells obtained from 6 subjects) identified physiological and COPD-relevant distal airway differentiation patterns, including distal airway-specific secretory phenotype (DASP) characterized with high expression of secretoglobins 3A2 and 3A1, surfactant proteins SFTPB and SFTPA2, and mucin 1, unique signatures of DABCs, and stromal (fibroblasts, smooth muscle, endothelial cell subpopulations) and immune (macrophage, T cells, B cell, mast cells). Immunofluorescence analysis and LCM confirmed distribution of cell type-specific markers with differential expression patterns of DABC and DASP signatures. Patient-derived DABC-stromal co-culture models reproduced 3 regenerative patterns: 1) physiological (high DABC-clonogenic potency, establishment of polarized differentiated organoids and DASP-expressing epithelia); 2) hypo-regenerative (failure of DABCs to form clones, spheres and mechanically stable differentiated epithelial barrier); and 3) hyperplastic (generation of DABC hyperplasia accompanied in some COPD samples by mucous-cell hyperplasia mimicking in vivo remodeling patterns). DISCUSSION/SIGNIFICANCE OF IMPACT: Patient-specific maps and models of distal airway regeneration patterns have been established in this study, which can be used to identify candidate pathways that mediate disease-relevant airway remodeling and potentially utilized as pre-clinical platforms for developing personalized therapeutic approaches to suppress the progression of distal airway remodeling in chronic lung diseases, including COPD.